Systematic review of self-assembling peptides as topical agents for treatment and prevention of gastrointestinal bleeding - Andrei Voiosu; Monica State; Victor Drăgan; Sergiu Văduva; Paul Bălănescu; Radu Bogdan Mateescu; Theodor Voiosu (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Gastrointestinal bleeding is a significant and potentially lethal event. We aimed to review the efficiency and safety of self-assembling peptides for the treatment and prevention of gastrointestinal tract bleeding. Methods We conducted a systematic search for studies describing the endoscopic use of self-assembling peptides for treatment or prevention of bleeding in the gastrointestinal tract in a parallel, independent fashion. The primary outcomes were rates of successful initial hemostasis, delayed bleeding, and rebleeding. The secondary outcomes were adverse events and ease and volume of gel used. Results Seventeen studies were analyzed. Overall success rate of self-assembling peptides in gastrointestinal bleeding was 87.7% (38%-100%), regardless of etiology or associated treatments. Rebleeding rate ranged from 0% to 16.2%, with a mean of 4.7%, and overall delayed bleeding rate was 5% (range, 0%-15.9%). Only three adverse events were reported in a pooled number of 815 patients. The volume of gel used varied (0.43 to 3.7 mL) according to indication and type of bleeding. Conclusions The limited available data on the use of self-assembling peptides in gastrointestinal endoscopy suggest a high efficiency and good safety profile.